Proces formování poslání na základě hlubšího pochopení firemního účelu - Slinták, Karel (Univerzita Pardubice, 2016)
Economy divided into a profitable and non-profit sector comes from the basic assumption that there are two types of organizations. Non-profit sector consists of organizations whose purpose is to solute social problems, while profitable sector is formed by enterprises whose purpose is to make money. The roots of this assumption lie in economic theories. In management theory there are also alternative views on the purpose of enterprises. The most famous is the hypothesis regarding the maximization of market value which reflects the economic model. Nowadays, however, it is growing interest in the social model that defines enterprises as social systems whose purpose is to serve society. The analysis of the theoretical attitudes revealed that profit or market value is not a sufficient response to what is the purpose of business organizations. Enterprises are instruments of society that satisfy different stakeholders. They are, like other organizations, set up in order to bring benefit to their environment. This benefit is formulated into a mission that represents the identity of the companies to all stakeholders. The mission is the intersection of society's needs and abilities of the company. Responsible companies therefore fulfilled their mission so that satisfy the needs of the market based on their competencies.
Rethinking Mission on the Basis of Deeper Understanding of Firm´s Purpose
Keywords: Market value; Mission; Profit; Purpose; Service to society; Theory of the business; M21; L21